5x+9+2x=23

Simple and best practice solution for 5x+9+2x=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+9+2x=23 equation:


Simplifying
5x + 9 + 2x = 23

Reorder the terms:
9 + 5x + 2x = 23

Combine like terms: 5x + 2x = 7x
9 + 7x = 23

Solving
9 + 7x = 23

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 7x = 23 + -9

Combine like terms: 9 + -9 = 0
0 + 7x = 23 + -9
7x = 23 + -9

Combine like terms: 23 + -9 = 14
7x = 14

Divide each side by '7'.
x = 2

Simplifying
x = 2

See similar equations:

| 3x^2-8x+7=0 | | 3.5=3.5+0.076x | | 4.5x-5.4=2.7x | | 5x+4(-4)=0 | | 4=p+2 | | x-2=6-3x | | x-5y=12 | | 2p=10.2 | | 3(2x+5)=6x+5 | | 5-(x+3)=-x+2 | | 12.85=y+4 | | -4x+(-1)=5 | | c-1.86=6.7 | | 3a^2-13a=-14 | | -4x+1=5 | | q-3=1 | | -4-0=5 | | y+9.59=19.59 | | 12x+11=10x+17 | | 6x-9=6(x-6) | | -4x+0=5 | | 2(4x-1)=8x-2 | | 0.6x+4=0.2x+5 | | 5x+9=x+69 | | 3(2x+2)+5x=2(4x-1)-2(-x+1) | | 8a^2-18=0 | | 5+18z=35z^2 | | 124x-x^5=79 | | 3(2-x)=7x+12-4x | | 124x-x^5=x^3-79 | | 1.3*3.14159265359*10.8= | | 6x-3=x+2+2x |

Equations solver categories